Gardening Series Scores Well With Agents; Senior Staff at International Research Centers - WIlliam F. Braden; Cynthia L. Garver; Olivia Vent (Journal of Applied Communications, 1982)
Two Research Briefs: Gardening Series Scores Well With Agents, by William F. Braden; and, Senior Communication Staff at International Centers, by Cynthia L. Garver, with Olivia Vent.